Photoelectrochemical sensor based on modified cadmium sulfide nanomaterials for copper (II) ions detection - Ibrahim, Izwaharyanie (2018)
Discovering the distinctive photophysical properties of semiconductor nanomaterials has made these a popular subject in recent advances in nanotechnology-related analytical methods. Semiconductors are well-known materials that have been widely used in photovoltaic devices such as optical sensors and bioimaging, and dye-sensitized solar cells (DSSCs), as well as for light-emitting diodes (LEDs). The use of a narrow-bandgap semiconductor such as cadmium sulfide nanoparticles (CdS NPs) in the photoelectrochemical (PEC) sensor of chemicals and biological molecules plays a key role as a photosensitizer and promotes some specific advantages in light-harvesting media. Their size-controlled optical and electrical properties make nanomaterials fascinating and promising materials for a variety of nanoscale photovoltaic devices. Moreover, charge injection from the narrow bandgap to the adjacent material leads to efficient charge separation and prolongs the electron lifetime by the elimination of the charge carrier recombination probability. In this regard, a single photon enables the production of multiple photogenerated charge carriers in CdS NPs, which subsequently boosts the effectiveness of the photovoltaic devices. In particular, this thesis highlights the recent emerging PEC detection based on CdS NPs, specifically related to the interactions of CdS NPs with target analytes of copper ions (Cu2+). The investigation and justification of different CdS nanocomposites were discussed in terms of different structural morphologies, and its impact on sensitivity and selectivity towards the targeted Cu2+ ions. Thus, it eventually provides a significant insight in achieving real-world applications of CdS-based PEC sensing. In the first studies, the nanospherical-like morphology of CdS with a narrow diameter distribution of about 350–400 nm was being employed and assembled with a transparent ultrathin reduced graphene oxide (rGO) layer. The nanostructured CdS adhered securely to a continuous network of rGO that also acted as an avenue to facilitate the transfer of electrons from the conduction band (CB) of CdS. The CdS-rGO photoelectrode response for Cu2+ ion detection had a linear range of 0.5–120 μM, with a limit of detection (LoD) of 16 nM. The low LoD demonstrated the favourable structure of CdS-rGO as photoactive materials in PEC sensing platform. In the second studies, the smaller particle diameters in an average of 25−30 nm of nanospherical CdS was obtained. The hydrothermal synthesis of CdS NPs were decorated with gold quantum dots (Au QDs) via stepwise in situ approaches, along with notable PEC performance. The introduction of Au which induced a plasmonic effect on photoactive materials like CdS semiconductors has prompted an intensive interest in PEC sensing applications. The hybrid structure of CdS-Au resulted in the amplification of the photocurrent signal because of the enhanced absorption of photon-generated photoelectron on the CdS. Therefore, it contributed to a sensitive Cu2+ ions detector with the lowest LoD of 6.73 nM in a linear range of 0.5−120 nM. In the third studies, huge efforts have been dedicated to intensifying the PEC performance by modifying the morphology and structure of CdS. Onedimensional (1D) nanostructure (e.g. nanotubes, nanorods, nanofiber and nanowire) of CdS were found to have a practical and substantial potential due to its specific directionality for the transportation of charge carrier, thus decreasing the probability of the recombination of charge carrier. In this regards, the 1D nanorods (NRs) structure of CdS was prepared and the outcomes consistently portray a much better PEC performance than the other counterpart particulate nanostructure. A multi-functional hybrid nanostructure of CdS NRs with Au NPs and graphene quantum dots (GQDs) has been successfully designed. The calculated LoD was 2.27 nM in a range of 0.1-290 nM. A clear trend can be observed based on the obtained LoD from all the three studies, and ultimately proven that the structure, particle size and the nanocomposite materials- based CdS could greatly influence the PEC sensing performance of Cu2+ ions. It has been a pressing need to develop a new materials for simultaneous detection and removal of Cu2+ ions from water sources, due to its acute and chronic effect on human health upon exposure to excessive copper. Thus, in the final studies, a ternary hybrid of cellulose acetate (CA) with CdS and methylene blue (MB) in a bead composition was synthesized and investigated as a photosensor-adsorbent of Cu2+ ions. The PEC detection of Cu2+ ions possessed a lower LoD of 16.9 nM and a notable removal efficiency of 96.3% in the linear range of 0.1-290 nM. Conclusively, these research have given rise to a neoteric finding and provided an important leap in the employment of CdS as potential semiconductor materials in PEC sensing applications. Even though, only a few CdS-based products that have successfully penetrated the market, but the thorough study and investigation of CdS- based nanocomposite in this thesis can eventually disclose its real potential. Ultimately, it may become a kick-start to researchers and innovators to come up with new CdS-based photosensor device.